2012
DOI: 10.1002/9781118433010.ch12
|View full text |Cite
|
Sign up to set email alerts
|

Fractographic Analysis of Broken Ceramic Dental Restorations

Abstract: Why did it break? Where is the origin? Did it break from an unexpected cause? Was there a problem with the material or was the crown or bridge simply overloaded? Was it misused? Was the crown fabricated properly? Was there a fitting problem? These are common practical questions and the fractographer can often give answers. Analysis of ceramic restorations can be difficult, but fractographic analysis is a cumulative learning experience. Our skill level is improving rapidly as we learn to recognize and interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Twelve of the thin-walled crowns did not survive cyclic loading at 250 N and the strength of the remaining eight specimens decreased. The fracture modes observed in the study resemble clinically observed failures [13,16,[26][27][28][29] and the fracture loads are close to or even below maximal biting force [30].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Twelve of the thin-walled crowns did not survive cyclic loading at 250 N and the strength of the remaining eight specimens decreased. The fracture modes observed in the study resemble clinically observed failures [13,16,[26][27][28][29] and the fracture loads are close to or even below maximal biting force [30].…”
Section: Discussionsupporting
confidence: 63%
“…The silicone cement was used in order to be able to remove the crowns from the abutment between the two test settings and in order to create hoop-stress cervically without causing contact damage between abutment and crown. The fractographic analyses of the specimens that fractured during dynamic loads reveal that they did actually fracture due to hoop stress as observed in clinical failures and in the static loading [4,13,16,26], indicating that the stress situation is similar to in vivo situations albeit not identical.…”
Section: Aging Proceduresmentioning
confidence: 86%
“…Most in‐vitro fracture tests of crowns reveal fractures induced by contact damage from the loading device , leading to the assumption that occlusal load causes ceramic crowns to fracture from the point of contact and also created a basis for many in‐vitro tests and finite element analyses . The failure modes found both in the present and in previous studies of crowns fractured during clinical function do not match the fracture modes found in vitro . Contact damage was seen as secondary damage or in cases of veneer chipping in clinical fractures.…”
Section: Discussionmentioning
confidence: 62%
“…This phenomenon is known as the Dugdale effect where polymer chains in the polymer phase spread plasticity under load as claimed by previous studies. (42,43) Conversely, UP.Cad and VS veneers in the present study revealed 20% and 40% catastrophic failure for 1mm and 1.5mm respectively; yet these rigid glassceramic yield stress concentration at critical areas that might be a reason of catastrophic fractures. (44) On the other side, radial cracks were originated from the cement interface of VS samples, propagated in the direction of the proximal margins or occlusally regardless to the occlusal thickness as shown in SEM (Figure 8).…”
Section: Discussionmentioning
confidence: 43%